The Effect of Organizational Commitment and Work Culture on Civil Servants Public Service Performance in Tomohon’s District Office - Sisca Rumambi; Evi Elvira Masengi; Wilson Bogar (Syntax Corporation Indonesia, 2022)
This study aims to explain the commitment to public service organizations of sub-district civil servants in Tomohon then the influence of work culture on public service performance using quantitative methods. The authors analyze and explain the influence of the variables in the research concept model. The study results indicate that the effect of Organizational Commitment on Public Service Performance shows a positive and significant direction. Employees who have a high organizational commitment must be selectively prepared from the start (recruitment). It is hoped that with the recruitment of employees with a merit system, employees with a high organization can carry out their functions, duties, and roles. The performance of public services shows results that organizational commitment and work culture simultaneously have a significant effect on employee performance. Moreover, the contribution of organizational commitment and work culture simultaneously to the performance of public services is 53.50%, while the other variable determines the remaining 46.50%. The conclusion of this study provides an overview of organizational and cultural commitment to the performance of civil servants as a sub-district public service in Tomohon; thus, the employees have continuity and respective roles following the existing sub-districts and functions.